Climate Change Affects Multiple Coral Reef Fisheries Ecosystem Services - Sarah M. Martin; James P. W. Robinson; Juliette Lucas; Emilie Augustin; Rodney Govinden; Shaun K. Wilson; Nicholas A. J. Graham (Fisheries Management and Ecology, 2025)
Coral reef fisheries support livelihoods and provide an affordable source of essential dietary nutrients to coastal people. However, climate‐driven coral bleaching is dramatically altering reef habitats and changing reef fish composition, diversity, and productivity. We used data from fisheries independent surveys and artisanal trap landings to explore how reefs with different responses to coral bleaching differed in habitat configurations, fisheries catch rates, economic returns, and nutritional content. Coral‐associated fishes supported the highest catch rates, greatest species diversity, highest rates of economic returns for fishers, and a wide price range for consumers. Macroalgae‐associated fishes supported the greatest overall fisheries yields, which indicated higher fishery dependence on these habitats. Nutrient content was high in catches across all habitats, but concentrations varied by nutrient, which suggested that fishing across a range of reef habitats should provide the greatest variety of nutrients to coastal communities.